Unveiling the Nexus Between Land Use, Land Surface Temperature, and Carbon Footprint: A Multi-Scale Analysis of Building Energy Consumption in Arid Urban Areas - Ammar Abulibdeh (15785928) (2024)
Urbanization and land use changes, especially in arid environments, significantly impact local climate and energy demand. This study investigates the relationship between Land Use/Land Cover (LULC) changes, Land Surface Temperature (LST), and the carbon footprint (CF) from building energy consumption in Doha, Qatar. Specifically, the study addresses the gap in understanding how LULC and LST interact to influence CF in arid urban areas. The research utilizes electricity consumption data from residential, commercial, and government buildings in conjunction with remote sensing data (Landsat 8) and climatical data (ERA5) to estimate LST and vegetation health. The Multiregional Input-Output (MRIO) model was employed to calculate the CF from direct and indirect energy consumption. At the same time, the support vector machine (SVM) was used to classify LULC into urban areas, green spaces, inland water bodies, and barren lands. To further investigate the spatial heterogeneity of the relationships between LST and climate variables, Multiscale Geographically Weighted Regression (MGWR) was utilized. This study hypothesizes that changes in LULC and LST will significantly increase the CF of buildings, especially during peak summer months in arid regions, while increased vegetation will help reduce this impact. CF hotspots are expected in areas with higher LST and less green space. The findings reveal significant correlations between higher LST, reduced green spaces, and increased CF in residential and commercial sectors. Villas and commercial buildings exhibited the highest CF during the summer due to increased cooling demands, with noticeable CF hotspots in specific urban areas. The study underscores the role of green spaces in mitigating both LST and CF, with the Normalized Difference Vegetation Index (NDVI) showing an inverse relationship to CF. Policy implications point to the urgent need for integrating urban greening initiatives, enhancing energy efficiency in building design, and revising urban planning policies to address the challenges posed by LST and rising energy demands in arid regions. Recommendations include incentivizing the adoption of energy-efficient building designs and improving vegetation cover to enhance urban resilience in arid climates. This study offers critical insights for policymakers, urban planners, and environmental managers aiming to balance urban growth with sustainable energy use and climate resilience. Other Information Published in: Earth Systems and Environment License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41748-024-00550-6